2009
DOI: 10.1111/j.1601-5037.2009.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of musculoskeletal disorders among Australian dental hygiene students

Abstract: Overall, this study suggests that MSD are a reasonably common problem for dental hygiene students in Australia. As such, further studies are required to establish epidemiological patterns of MSD, and our profession will need to carefully consider preventive strategies to help minimize the impact of this important occupational health issue on the next generation of dental hygienists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 26 publications
9
66
4
1
Order By: Relevance
“…This prevalence rate is in general agreement with the prevalence rates reported in the literature for college students which vary between 32.9% and 89.3% [6][7][8][9][10][11][13][14][15][16]18,19 . It is however higher than the 32.9% 8 and 36.9% 9 reported among nursing students in Japan, and lower than the 73.3% 18 and 80.0% 19 reported among nursing students in Korea and Australia respectively, as well as the reported prevalence among nurses at the workplace (i.e 78-84.4%) [30][31][32][33] .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 90%
See 2 more Smart Citations
“…This prevalence rate is in general agreement with the prevalence rates reported in the literature for college students which vary between 32.9% and 89.3% [6][7][8][9][10][11][13][14][15][16]18,19 . It is however higher than the 32.9% 8 and 36.9% 9 reported among nursing students in Japan, and lower than the 73.3% 18 and 80.0% 19 reported among nursing students in Korea and Australia respectively, as well as the reported prevalence among nurses at the workplace (i.e 78-84.4%) [30][31][32][33] .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 90%
“…Despite an elevated prevalence of MSDs in this population, the prevalence of MSDs in the different body regions is lower than that reported in previous studies with similarly high prevalence rates of MSDs among college students 7,11,[13][14][15]18,19 . Besides that, the clustering pattern of MSDs particularly in the neck (28.0%), upper back (27.4%), lower back (23.6%), wrists/hand (22.9%) and hip/thigh (21.0%) observed from this study is somewhat different compared with findings in previous studies among nursing students 18,19 .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015contrasting
confidence: 79%
See 1 more Smart Citation
“…Musculoskeletal disorders (MSD) are injuries to the human support system that may occur due to a single or multiple traumas (5). Dentists have reported musculoskeletal disorders for decades (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews across the world have shown a high prevalence of MSD among dentists (Lehto et al, 1991;Lindfors et al, 2006;Hayes et al, 2009;Morse et al, 2010). Dentists assume static postures at work which require more than 50% of the body's muscle to contract while resisting gravity (Valachi and Valachi, 2003).…”
Section: Prevalence Of Musculoskeletal Disorders In Dentistrymentioning
confidence: 99%